Nationwide database analysis of one-year readmission rates after open surgical or thoracic endovascular repair of Stanford Type B aortic dissectionCentral MessagePerspective - John A. Treffalls, BS; Christopher B. Sylvester, PhD; Umang Parikh, MD; Rodrigo Zea-Vera, MD; Christopher T. Ryan, MD; Qianzi Zhang, MS; Todd K. Rosengart, MD; Matthew J. Wall, MD; Joseph S. Coselli, MD; Subhasis Chatterjee, MD; Ravi K. Ghanta, MD (JTCVS Open, 2022)
Objective: We examined readmissions and resource use during the first postoperative year in patients who underwent thoracic endovascular aortic repair or open surgical repair of Stanford type B aortic dissection. Methods: The Nationwide Readmissions Database (2016-2018) was queried for patients with type B aortic dissection who underwent thoracic endovascular aortic repair or open surgical repair. The primary outcome was readmission during the first postoperative year. Secondary outcomes included 30-day and 90-day readmission rates, in-hospital mortality, length of stay, and cost. A Cox proportional hazards model was used to determine risk factors for readmission. Results: During the study period, type B aortic dissection repair was performed in 6456 patients, of whom 3517 (54.5%) underwent thoracic endovascular aortic repair and 2939 (45.5%) underwent open surgical repair. Patients undergoing thoracic endovascular aortic repair were older (63 vs 59 years; P < .001) with fewer comorbidities (Elixhauser score of 11 vs 17; P < .001) than patients undergoing open surgical repair. Thoracic endovascular aortic repair was performed electively more often than open surgical repair (29% vs 20%; P < .001). In-hospital mortality was 9% overall and lower in the thoracic endovascular aortic repair cohort than in the open surgical repair cohort (5% vs 13%; P < .001). However, the 90-day readmission rate was comparable between the thoracic endovascular aortic repair and open surgical repair cohorts (28% vs 27%; P = .7). Freedom from readmission for up to 1 year was also similar between cohorts (P = .6). Independent predictors of 1-year readmission included length of stay more than 10 days (P = .005) and Elixhauser comorbidity risk index greater than 4 (P = .033). Conclusions: Approximately one-third of all patients with type B aortic dissection were readmitted within 90 days after aortic intervention. Surprisingly, readmission during the first postoperative year was similar in the open surgical repair and thoracic endovascular aortic repair cohorts, despite marked differences in preoperative patient characteristics and interventions.